Design and evaluation of a Flight Envelope Protection haptic feedback system. Issue 19 (2016) - Ellerbroek, J.; Martin, M.J.M. Rodriguez; Lombaerts, T.; van Paassen, M.M.; Mulder, M.
Abstract: This paper describes the design and evaluation of a shared control, haptic feedback system to communicate Flight Envelope Protection System intent. The concept uses a combination of stiffness feedback and vibration to communicate proximity of the aircraft state to flight envelope boundaries. In addition, a stick center shift can be applied by the envelope protection system to cooperatively perform corrective actions in case of severe excursions of the envelope margins. Results from the evaluation experiment show improved performance with haptic feedback in both scenarios. Workload ratings were unaffected. Pilot opinion was unanimously positive, especially with regard to the combination of stiffness feedback and vibration cues.